2017
DOI: 10.1117/12.2252407
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the microcirculation of atopic dermatitis using angiographic optical coherence tomography

Abstract: Background and Aim: With inflammatory skin conditions such as atopic dermatitis (AD), epidermal thickness is mediated by both pathological hyperplasia and atrophy such as that resulting from corticosteroid treatment. Such changes are likely to influence the depth and shape of the underlying microcirculation. Optical coherence tomography (OCT) provides a non-invasive view into the tissue, however structural measures of epidermal thickness are made challenging due to the lack of a delineated dermal-epidermal jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previously we have shown that measurable morphological differences between healthy and AD scans are attainable using svOCT depth projections over a wide depth range (30-300μm) [32], however it is unclear if the differences were related to true morphological differences or simply a result of the AD vessels being much deeper in the skin. To investigate this, the SPD data from Sec.…”
Section: The Effect Of Severity On Vascular Morphology In the Superfimentioning
confidence: 96%
See 1 more Smart Citation
“…Previously we have shown that measurable morphological differences between healthy and AD scans are attainable using svOCT depth projections over a wide depth range (30-300μm) [32], however it is unclear if the differences were related to true morphological differences or simply a result of the AD vessels being much deeper in the skin. To investigate this, the SPD data from Sec.…”
Section: The Effect Of Severity On Vascular Morphology In the Superfimentioning
confidence: 96%
“…1, the capillary loop depth (CLD) and superficial plexus depth (SPD) within skin could potentially be used as a robust measure of acanthosis (epidermal hypertrophy). In our previous work, measurements of CLD and SPD were acquired qualitatively through visual observation of an en-face flythrough of the corresponding angiographic data [32]. Here, the skeletonization procedure outlined in Sec.…”
Section: Automatic Quantification Of Vascular Depthmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is gaining acceptance as a useful device to aid in the diagnosis of basal cell carcinoma, as well as for research into many skin conditions and their treatments. [9][10][11][12][13][14] OCT was first described by Huang and coworkers at Massachusetts Institute of Technology (MIT) in 1991 and has been very successfully applied to the field of ophthalmology for imaging the subsurface structures of the retina and other avascular parts of the eye. 15 Welzel et al reported the use of OCT to obtain structural images of the most superficial layers skin.…”
Section: New Technique For Visualizing Blood Vesselsmentioning
confidence: 99%
“…AD was studied with OCT in two studies [47,48]. In patients with known AD, acanthosis was assessed by measurements of superficial plexus depth in patients with healed flares.…”
Section: Resultsmentioning
confidence: 99%
“… Epidermal spongiosis, lymphocyte exocytosis, stratum corneum disruption, and parakeratosis are characteristic of contact dermatitis in RCM and OCT [15,37‐46,68]. Acanthosis, thickened epidermis, and dilated blood vessels are associated with AD using angiographic OCT and MPM [47‐51]. Perinuclear mitochondria and spongiosis are also observed using MPM only [49‐51].…”
Section: Resultsmentioning
confidence: 99%